2022
DOI: 10.1155/2022/6268755
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annurca Flesh Apple Polyphenols in Human Thyroid Cancer Cell Lines

Abstract: Among natural macromolecules, the polyphenol extract from Annurca flesh (AFPE) apple could play a potential therapeutic role for a large spectrum of human cancer also by exerting antioxidant properties. Thyroid cancer is a common neoplasia in women, and it is in general responsive to treatments although patients may relapse and metastasize or therapy-related side effects could occur. In this study, we explored the effects of AFPE on papillary (TPC-1) and anaplastic (CAL62) thyroid cancer cell line proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…In contrast, only one study using pretreatment with AFPE showed a reduction in cell death induced by oxidative stress, underlying that polyphenols found specifically in this source may (alone or in combination) show a protective effect in this specific scenario (13). Finally, cell cycle and apoptosis regulators, inflammatory cytokines, inductors of cell growth, signaling pathways and altered mitochondrial membrane potentiality were also associated to the causing of cell death in TPC-1 lineage (6)(7)(8)(9)(10)(11)(12)(13)15). Therefore, it is possible to consider that many polyphenolic compounds have antineoplastic properties specifically in TPC-1 cell lineage.…”
Section: Therapeutic Potentialsmentioning
confidence: 84%
See 3 more Smart Citations
“…In contrast, only one study using pretreatment with AFPE showed a reduction in cell death induced by oxidative stress, underlying that polyphenols found specifically in this source may (alone or in combination) show a protective effect in this specific scenario (13). Finally, cell cycle and apoptosis regulators, inflammatory cytokines, inductors of cell growth, signaling pathways and altered mitochondrial membrane potentiality were also associated to the causing of cell death in TPC-1 lineage (6)(7)(8)(9)(10)(11)(12)(13)15). Therefore, it is possible to consider that many polyphenolic compounds have antineoplastic properties specifically in TPC-1 cell lineage.…”
Section: Therapeutic Potentialsmentioning
confidence: 84%
“…(2022) applied it in a 24 hours exposition with a concentration of up to 250 μM/mL, resulting in a reduction of cell viability and promotion of cell cycle arrest analyzed by flow cytometry. Another concentration of AFPE (500 μM/mL) in a 20 hours exposition was evaluated by the DCFDA/H2DCFDA -Cellular ROS Assay Kit, obtaining a reduction of cell death induced by oxidative stress, contrasting with the findings described so far (13).…”
Section: Therapeutic Potentialsmentioning
confidence: 91%
See 2 more Smart Citations
“…To date, this is the first study evaluating the potential ability of Annurca apple extract to counteract oxidative stress in HFDPCs. However, previous investigations have demonstrated the protective effect of Annurca against ROS on other cell lines, such as anaplastic thyroid cancer cells (CAL62) [ 36 ] and mammary epithelial cells (MCF10A) cells [ 37 ]. These results indicate that AT HAIR‐FUL AA ® can impede H 2 O 2 ‐treated HFDPC ROS accumulation and apoptosis and, therefore, may be used as a potential supplement for preventing hair loss induced by oxidative stress.…”
Section: Resultsmentioning
confidence: 99%